Computational chemistry: reviews of current trends - Leszcynski, Jerzy (World Scientific, 2000)
The gap between experimental objects and models for calculations in chemistry is being bridged. The size of experimental nano-objects is decreasing, while reliable calculations are feasible for larger and larger molecular systems. The results of these calculations for isolated molecules are becoming more relevant for experiments. However, there are still significant challenges for computational methods. This series of books presents reviews of current advances in computational methodologies and applications.